2021
DOI: 10.1002/smll.202102884
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Integration of Chiral Lead–Chloride Perovskite Crystals with Si Wafer for Boosted Circularly Polarized Light Detection in Solar‐Blind Ultraviolet Region

Abstract: source in quantum optics, magnetic memory devices, and high-definition imaging. [4][5][6][7] For those CPL-based devices it is necessary to distinguish between two polarization states of CPL, that is, to establish sensitive CPL detectors. Different from the indirect method of detecting CPL, chiral material can enable direct CPL detectors without the assistance of optical elements, meeting the demands for integrated and flexible devices.One of the grand challenges for direct CPL detectors is seeking suitable ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…The findings indicate that the performance of our Co 2+ -doped (PEA) 2 PbI 4 device is superior to the reported results in systems similar to those of CPL detectors. [30,43] detector indicates that magnetic metal doping induces a long spin relaxation lifetime of the spin electrons generated by the absorption of σillumination, [27] which is consistent with the result of CPL absorption in Figure 5b. The selectivity for CPL detection in our devices was further confirmed by the optical switching characteristics (Figure 5d,e), which also revealed superior good stability and reversibility of our devices.…”
Section: Resultssupporting
confidence: 81%
“…The findings indicate that the performance of our Co 2+ -doped (PEA) 2 PbI 4 device is superior to the reported results in systems similar to those of CPL detectors. [30,43] detector indicates that magnetic metal doping induces a long spin relaxation lifetime of the spin electrons generated by the absorption of σillumination, [27] which is consistent with the result of CPL absorption in Figure 5b. The selectivity for CPL detection in our devices was further confirmed by the optical switching characteristics (Figure 5d,e), which also revealed superior good stability and reversibility of our devices.…”
Section: Resultssupporting
confidence: 81%
“…Spin polarized excitons are separated by a built-in electric field originating from the heterojunction in the photodiode architecture. 82,84 As a low-dimensional metal halide semiconductor, a CMHS has a large exciton binding energy, which leads to a high exciton recombination rate and difficulty in the separation of photogenerated charges. Recently, it was found that a CMHS-based heterojunction has interlayer exciton coupling 85 and controlled valley polarization.…”
Section: Spin-polarized Excitonics and Electronicsmentioning
confidence: 99%
“…86 A heterojunction based CPD combined a built-in electric field and CISS effect, which is expected to show a higher resolution of circularly polarized light. The ( R -MPA) 2 PbCl 4 /Si heterojunction 82 has a defect density of states (3.9 ± 2.2) × 10 10 cm −3 comparable to that of the ( R -MPA) 2 PbCl 4 single crystal ((2.0 ± 1.8) × 10 10 cm −3 ), and has a shorter PL lifetime (3.2 ns) than the ( R -MPA) 2 PbCl 4 single crystal, indicating that the ( R -MPA) 2 PbCl 4 /Si heterojunction has a lower spin-polarized exciton recombination rate. In the CPD based on ( R -MPA) 2 PbCl 4 /Si (the device structure in Fig.…”
Section: Spin-polarized Excitonics and Electronicsmentioning
confidence: 99%
“…Unlike indirect detection which requires optical elements, direct detection of CPL by chiral materials with intrinsic advantages can be exploited for integration in more applications [9]. Directly detectable electronic circuits for CPL can be created by a heterojunction photodiode [10][11][12], field-effect transistor [9], and plasmon resonance [13] to distinguish between different polarization states of CPL. Chiral organic semiconductors can be integrated as the photoactive layer in bulk heterojunction photodiodes to convert CPL into a polarization-dependent photocurrent [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Chiral organic semiconductors can be integrated as the photoactive layer in bulk heterojunction photodiodes to convert CPL into a polarization-dependent photocurrent [10,14]. Chiral hybrid organic-inorganic perovskites induce chirality into inorganic sublattice band edge states for efficient charge transport [11]. Chiral metamaterials based on plasmonic elements generate photocurrent from hot carrier generation and injection [13].…”
Section: Introductionmentioning
confidence: 99%